Participation of actin filaments in the response of Arabidopsis thaliana root cells to low-temperature action - Plohovska, S.G.; Zaslavsky, V.A.; Yemets, A. I.; Blume, Ya.B. (Reports of the National Academy of Sciences of Ukraine, 2015)
The effect of the low temperature (4 ºC) on the organization of actin filaments (microfilaments) of cells of different growth zones of the root of Arabidopsis thaliana (L.) is studied. For the visualization of these structures and detailed in vivo analysis of the changes in their structure, the line A. thaliana expressing the chimeric gene gfp-abd2-gfp was used. It is found that cold treatment inhibits growth of the main root and gives its morphology, causing a large number of deformed (ectopic) root hairs in the zone of differentiation. The temporal relationship of the disorientation and the organization of actin filaments and the detected changes of growth and morphology of roots under conditions of cold factor is shown. It is found that the most sensitive to the effects of the cold actin filaments are meristematic cells and all epidermal cells of the root zone of A. thaliana.